2021
DOI: 10.5606/tgkdc.dergisi.2021.20366
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative arrhythmias in patients undergoing congenital heart surgery

Abstract: Background This study aims to evaluate early postoperative arrhythmias in children undergoing congenital cardiac surgery. Methods A total of 670 pediatric patients (355 males, 315 females; median age: 4 months; range, 1 day to 18 years) who underwent cardiac surgery due to congenital heart defects between December 2018 and November 2019 were included. The rate of postoperative arrhythmias, diagnosis, potential risk factors, and management strategies were evaluated. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
2
10
0
3
Order By: Relevance
“…Arrhythmia after cardiac surgery is one of the common and serious postoperative complications, with an incidence of 7.5% to 48% [20][21][22]. Most arrhythmic events occur in the early postoperative period [23], due to direct damage or manipulation of the cardiac conduction system during surgery, or due to myocardial edema and in ammation near the conduction system. High postoperative catecholamine levels and electrolyte disturbances are also possible causes, and prolonged myocardial dysfunction due to pressure or volume overload also makes these patients particularly vulnerable to arrhythmias [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhythmia after cardiac surgery is one of the common and serious postoperative complications, with an incidence of 7.5% to 48% [20][21][22]. Most arrhythmic events occur in the early postoperative period [23], due to direct damage or manipulation of the cardiac conduction system during surgery, or due to myocardial edema and in ammation near the conduction system. High postoperative catecholamine levels and electrolyte disturbances are also possible causes, and prolonged myocardial dysfunction due to pressure or volume overload also makes these patients particularly vulnerable to arrhythmias [24].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias after cardiac surgery are mostly atrial brillation [25], and Echahidi et al showed that the overall incidence of arrhythmias after cardiac surgery is 60.2%, the most common type is atrial brillation (35.0%), and atrial brillation after valve surgery is about 40%, followed by conduction block (5.3%) [26].In this study, atrial brillation accounted for 73.91% of total arrhythmia, new atrial brillation occurred in 40.9% after valve surgery, and one patient developed sinus arrest and junctional rhythm after surgery and was successfully discharged through medical pacemaker treatment.Many studies have now shown that advanced age, race, gender, history of myocardial infarction, obesity, metabolic syndrome, and left atrial diameter 45 mm are considered risk factors for postoperative arrhythmias [27][28][29].Age, operation time, CPB time, and aortic cross-clamp time were independent risk factors for postoperative arrhythmia [23,30].This study showed that age, weight, BMI, diabetes, NYHA class, LAD, LVDs, RVDs, TBIL, DBIL, UA, RDW, operation time, CPB time, aortic cross-clamp time, and operation type were associated with arrhythmia after robotic heart surgery, and further multivariate regression analysis indicated that preoperative DBIL level and aortic cross-clamp time were independent risk factors.Preoperative DBIL levels re ect the ability of liver cells to transform indirect bilirubin in cardiac patients, and some patients with heart disease have poor preoperative cardiac function, resulting in hepatic congestion further leading to hepatocyte injury, and such patients have poor preoperative cardiac function, which may lead to postoperative arrhythmia.It has been con rmed that preoperative DBIL level is an independent predictor of atrial brillation after cardiac surgery [31], and bilirubin level may be associated with recurrence after cardiac atrial brillation ablation [32].The relationship between atrial diameter and postoperative atrial brillation has been demonstrated [33], but this study found signi cant differences in preoperative atrioventricular structure between patients with and without arrhythmia, but did not con rm its independent risk factors.Aortic crossclamp time is closely related to myocardial ischemia-reperfusion injury, and a large number of studies have shown that it is an independent risk factor for a variety of postoperative complications.This study showed that aortic crossclamp time was an independent risk factor for arrhythmia after robotic cardiac surgery, which was consistent with previous studies. Accurate intraoperative operation shortened myocardial ischemia time, which was a key factor to reduce postoperative arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmia after cardiac surgery is one of the common and serious postoperative complications, with an incidence of 7.5-48% [20][21][22]. Most arrhythmic events occur in the early postoperative period [23], due to direct damage or manipulation of the cardiac conduction system during surgery, or due to myocardial edema and in ammation near the conduction system. High postoperative catecholamine levels and electrolyte disturbances are also possible causes, and prolonged myocardial dysfunction due to pressure or volume overload also makes these patients particularly vulnerable to arrhythmias [24].…”
Section: Discussionmentioning
confidence: 99%
“…, and Echahidi et al showed that the overall incidence of arrhythmias after cardiac surgery is 60.2%, the most common type is atrial brillation (35.0%), and atrial brillation after valve surgery is about 40%, followed by conduction block (5.3%)[26].In this study, atrial brillation accounted for 73.91% of total arrhythmia, new atrial brillation occurred in 40.9% after valve surgery, and one patient developed sinus arrest and junctional rhythm after surgery and was successfully discharged through medical pacemaker treatment.Many studies have now shown that advanced age, race, gender, history of myocardial infarction, obesity, metabolic syndrome, and left atrial diameter 45 mm are considered risk factors for postoperative arrhythmias[27- 29].Age, operation time, CPB time, and aortic cross-clamp time were independent risk factors for postoperative arrhythmia[23,30].This study showed that age, weight, BMI, diabetes, NYHA class, LAD, LVDs, RVDs, TBIL, DBIL, UA, RDW, operation time, CPB time, aortic cross-clamp time, and operation type were associated with arrhythmia after robotic heart surgery, and further multivariate regression analysis indicated that preoperative DBIL level and aortic cross-clamp time were independent risk factors.Preoperative DBIL levels re ect the ability of liver cells to transform indirect bilirubin in cardiac patients, and some patients with heart disease have poor preoperative cardiac function,…”
mentioning
confidence: 99%
“…14 Furthermore, a cohort study in 2021 showed that the frequency and diagnosis of arrhythmias might differ depending on the type of cardiac procedure. 16 A study in Switzerland found that various variables could cause or aggravate postoperative arrhythmias. These variables included pre-existing myocardial compromise due to cardiac defects, complex procedures with extensive scars and suture lines, consequences of myocardial ischemia, postoperative electrolyte disturbances, and increased adrenergic tone or catecholamine stimulation.…”
mentioning
confidence: 99%